Papvimochneshwar Temple - Mumbai Archive Project Team (Jio Institute, 2024)
Papvimochneshwar Temple was founded on 18 August 1904 and has retained much of its traditional architecture. The temple entrance features a pair of deepastambhs (lamp columns) flanking the entrance and a tulsi holy basil) planter (on the left).